2019
DOI: 10.22201/ib.20078706e.2019.90.2769
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macroinvertebrate community diversity of Montebello Lakes, Chiapas

Abstract: Benthic macroinvertebrate community biodiversity of tropical lakes has been rarely addressed. The present study recognizes the taxonomic diversity of the deep benthic macroinvertebrate communities of 18 lakes of the Protected Natural Area "Lagunas de Montebello", Chiapas, Mexico. The lakes display different morphometric features and trophic states. Five sampling campaigns were carried out between 2013 and 2016. Forty-nine taxa (14 orders, 25 families, 40 identified genera, and 9 undetermined taxa) were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
3
6
2
Order By: Relevance
“…Rotifer inventories of Mexican inland waters report species richness values of 10-125 in rivers [9,11], 7-60 in reservoirs [7][8][9], 10-65 in oligotrophic [10,45], and 35-80 in eutrophic lakes [9,12]; however, our 21 pelagic rotifer species richness for the PNLM lakes is on the lower limit of those ranges. It is noteworthy that the low biodiversity recorded in the pelagic rotifer assemblage from the lakes of the PNLM matches the low biodiversity reports for other biological assemblages (e.g., benthic macroinvertebrates [46]) of these same lakes. At a regional scale, the study of Arroyo-Castro et al [15] in 17 sinkholes from the Cozumel Island, Quintana Roo, showed 36 rotifer species richness, ranging from 0 to 19 species per water body.…”
Section: Discussionsupporting
confidence: 76%
“…Rotifer inventories of Mexican inland waters report species richness values of 10-125 in rivers [9,11], 7-60 in reservoirs [7][8][9], 10-65 in oligotrophic [10,45], and 35-80 in eutrophic lakes [9,12]; however, our 21 pelagic rotifer species richness for the PNLM lakes is on the lower limit of those ranges. It is noteworthy that the low biodiversity recorded in the pelagic rotifer assemblage from the lakes of the PNLM matches the low biodiversity reports for other biological assemblages (e.g., benthic macroinvertebrates [46]) of these same lakes. At a regional scale, the study of Arroyo-Castro et al [15] in 17 sinkholes from the Cozumel Island, Quintana Roo, showed 36 rotifer species richness, ranging from 0 to 19 species per water body.…”
Section: Discussionsupporting
confidence: 76%
“…Recently, [12] explained that the closeness between lakes and the high environmental heterogeneity promoted species turnover, resulting in the large regional diversity but great singularity level among the benthic macroinvertebrates of the "Lagunas de Montebello" National Park lakes. The same large regional diversity but great singularity in these lakes have been reported for the zooplankton and benthic macroinvertebrates communities [10,11,60].…”
Section: Discussionsupporting
confidence: 75%
“…If the increasing human activities in the area lead to the loss of just a single lake's biodiversity, the result is a reduction in the regional biodiversity. Similar high regional diversities on the pelagic rotifer [11] and benthic macroinvertebrate [10] assemblages suggest this is a characteristic diversity pattern of the "Lagunas de Montebello" National Park Lake District.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations